A design of self-learning intelligent infrared remote controller. Issue 1 (February 2021) - Lu, An; Gong, Yingkun; Xiong, Deyi
Abstract: This paper presents a self-learning intelligent infrared remote control system for Android system. In this paper, STM32F103RCT6 chip is selected as microprocessor, infrared integrated receiver head VS1838 and infrared light emitting diode are used as infrared receiving/transmitting module. The communication of experimental platform system is established to realize the management and control of household appliances by mobile terminal.